Effects of graded levels of boiled rubber (Hevea brasiliensis) seeds meal on growth and carcass characteristics of rabbits - Amandine, Matho (Indian Journal of Animal Nutrition, 2021)
The prices of various feed ingredients in recent years have risen to the extent that the cost of feed is now very high, making animal production more expensive and its products inaccessible. The present study was conducted at the Teaching and Research Farm of the University of Dschang-Cameroon, in order to evaluate the effects of inclusion level of rubber seed meal (RSM) on growth performances and carcass characteristics in rabbits. 60 rabbits (30 males and 30 females) aged 2 months and weighing 900 ± 80 g were randomly assigned to the 5 rations, that is 12 rabbits (6♀ and 6♂) for each ration, in a completely randomized design. The 1st group received ration free from RSM (T0); the 2nd group received ration containing 20% of raw RSM (R20); and the 3rd, 4th and 5th groups received rations containing respectively 20, 25 and 30% of boiled RSM (B20, B25 and B30). The feed intake (FI) and live weight (LW) were collected weekly for 3 Months. At the end of the trial, 8 rabbits (4 males and 4 females) per treatment were randomly selected and slaughter for carcass characteristics evaluation. The main results showed that the FI and the feed conversion ratio (FCR) decreased insignificantly (p>0.05) in rabbits fed with rations containing boiled RSM (B30 for the FI and B25 for the FCR) compared to those receiving T0 ration. Contrary, the live weight and weight gain increased insignificantly (p>0.05) in rabbits fed with the B25 ration compared to those receiving T0 and R20 rations. The carcass yield, the weights of liver, kidneys, heart, abdominal fat, caecum, big intestine, ileum, and the lengths of ileum and big intestine were comparable (p>0.05) among rations. The kg of feed cost 184.17 and 180.25 CFAF, respectively for B25 and B30 rations, that is a reduction of 17.51 and 19.26% compared to T0 (223.25 CFAF). The production cost of a kg of live weight was 1676.61, 1084.76 and 1130.17 CFAF, respectively for T0, B25 and B30 rations. Therefore, the inclusion of boiled RSM in feed increased the growth performances and reduced the cost of production. Hence, rubber seeds can be used in rabbit feeding, until 25% in the ration, without affecting negatively their growth performances.